The putative autophagy regulator Atg7 affects the physiology and pathogenic mechanisms of Cryptococcus neoformans. (November 2016) - Oliveira, Debora L; Fonseca, Fernanda L; Zamith-Miranda, Daniel; Nimrichter, Leonardo; Rodrigues, Jéssica; Pereira, Marcos D; Reuwsaat, Julia CV; Schrank, Augusto; Staats, Charley; Kmetzsch, Livia; Vainstein, Marilene H; Rodrigues, Marcio L
Aim: We investigated the involvement of the autophagy protein 7 (Atg7) in physiology and pathogenic potential of Cryptococcus neoformans .Materials & methods: The C. neoformans gene encoding Atg7 was deleted by biolistic transformation for characterization of autophagy mechanisms, pigment formation, cell dimensions, interaction with phagocytes and pathogenic potential in vivo .Results & conclusion: ATG7 deletion resulted in defective autophagy mechanisms, enhanced pigmentation and increased cellular size both in vitro and in vivo . The atg7Δ mutant had decreased survival in the lung of infected mice, higher susceptibility to the killing machinery of different host phagocytes and reduced ability to kill an invertebrate host. These results connect Atg7 with mechanisms of pathogenicity in the C. neoformans model.